Making Foreign Investment Contributory to Sustainable Development in Ethiopia: A Normative Analysis. - Fentie, Woldetinsae (Bahir Dar University Journal of Law, 2024)
To ensure positive impacts of Foreign Direct Investment (hereinafter FDI) to domestic human good, it has become imperative for host states to identify responsibility of foreign investors to sustainable development and devise mechanisms to effectuate the same. However, this task poses challenges for least developed countries like Ethiopia, which must balance the competing interests of attracting foreign capital and pursuing sustainability objectives. The governance of FDI is a highly debated subject within the international investment regime. It is currently threatened by legitimate crisis, requiring a concerted, well-crafted and comprehensive response from varying actors in the FDI landscape. This paper suggests that if FDI is appropriately managed, guided, and regulated, it is possible not only to minimize its impairment on sustainability but can also contribute to sustainable development. The paper qualitatively explores potential approaches within the existing framework of norms in the Ethiopian legal system to establish the sustainable development responsibilities of foreign investors. While treaty terms and contents are often influenced by global power dynamics, leaving little room for least developed countries like Ethiopia, the current global backlash against the regime could be taken as opportunity for reform. Drawing insights from the treaty practices of other states and by aligning itself with reform forces in the international investment regime, Ethiopia can strategically move to capitalize on the advantageous conditions. Findings of this paper suggests that, together with reform in the investment treaty regime, exhausting alternative measures could help the country install sustainable development friendliness in the existing frameworks.